International multi-centre study of pregnancy outcomes with interleukin-1 inhibitors. (23rd August 2017) - Youngstein, Taryn; Hoffmann, Patrycja; Gül, Ahmet; Lane, Thirusha; Williams, Rene; Rowczenio, Dorota M.; Ozdogan, Huri; Ugurlu, Serdal; Ryan, John; Harty, Len; Riminton, Sean; Headley, Alex P.; et al.
Abstract: Objective: To provide outcome data concerning pregnancies exposed to the Interleukin-1 (IL-1) inhibitors prior to conception in both men and women, during pregnancy and breast feeding. Methods: Retrospective data were collected from members of the International Society for Systemic Autoinflammatory diseases and collated in a single centre. A uniform data collection sheet was used to obtain standardized data including maternal age and diagnosis, type, duration of and response to IL-1 blockade, pregnancy duration, delivery, mode of feeding and neonatal development. Results: There were 31 maternal-exposed pregnancies from seven countries and we report the first data on paternal exposure: six to anakinra and five to canakinumab, with no negative outcomes. We also report the first data on canakinumab-exposed pregnancies: eight pregnancies that resulted in the delivery of seven healthy infants of normal gestational age and birthweight. There were 23 anakinra-exposed pregnancies resulting in the birth of 21 healthy infants, and one baby with unilateral renal agenesis and ectopic neurohypophysis. There were two first trimester miscarriages affecting a mother with active disease. There were no serious neonatal infections. Fourteen infants were breast fed with no complications. There were no reports of developmental delay, with follow-up of up to 10 years (median 18 months). Conclusion: This series substantially increases the published experience of IL-1 blockade and reproduction including the first data on canakinumab and on paternal exposure to these agents. Data are generally reassuring, although the case of renal agenesis is the second reported in an anakinra-exposed pregnancy.